THE INCREASED RISK OF RANDOM BLOOD GLUCOSE, BODY MASS INDEX AND ABDOMINAL CIRCUMFERENCE IN THE SCHIZOPHRENIC PATIENTS USING CLOZAPINE AND QUETIAPINE - Hidayah, Lailatul; Darmawan, Endang; Yuliani, Santi (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
The use of atypical antipsychotics often causes an increase in blood glucose levels, body mass index (BMI) and abdominal circumference. This study aims to identify the increased risk of random blood glucose, BMI and abdominal circumference in the schizophrenic patients using clozapine and quetiapine. This cohort study involved 35 schizophrenic patients (19 patients used clozapine and 16 patients used quetiapine). The measurement of random blood glucose BMI and abdominal circumference was done in the zero month, the first month and the second month. The average of random blood glucose, BMI and abdominal circumference were analyzed using Wilcoxon and Chi-square. In the use of clozapine, there is a significant increase in the average of random blood glucose between the first month and the second month (p=0.1) with the difference of 6.37 mg/dl, there is an increase average in BMI between the first month and the second month (p=0.03) with the difference of 0.18 kg/m² and an average increase in abdominal circumference between the zero month and the first month (p=0.04) with the difference of 1.47 cm, between the first month and the second month (p=0.02) with the difference of 1.94 cm. In the use of quetiapine, a significant increase in abdominal circumference between the first month and the second month (p=0.02) with the difference 1.38 cm. The use of clozapine has more risk in increasing random blood glucose (OR 2.00: CI 95% 0.41-9.76), BMI (OR 2.78: CI 95% 0.69-11.10) and abdominal circumference (OR 3.61: CI 95% 0.89-14.64) compared to the use of quetiapine. The use of clozapine has more risk in increasing blood glucose, BMI and abdominal circumference compared to the use of quetiapine.